Job Satisfaction and Organizational Commitment of Library Personnel in Public Universities in Nigeria - Omobola O, Adewoyin; Nkechi Ikonne, Chinyere; Madukoma, Ezinwanyi (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2020)
Purpose: The purpose of the study is to determine the influence of job satisfaction on organizational commitment of library personnel in public universities in South-West Nigeria. Design/methodology/approach: Cross-sectional survey research design was adopted for the study. Total enumeration was used. Data were collected using a validated questionnaire. Data were collected using a validated questionnaire. Descriptive statistics such as frequency, percentages, mean and standard deviation were also used to analyze the research questions while inferential statistics such as multiple regression analysis were used to test the hypotheses. Findings: Findings showed that job satisfaction had significant influence on organizational commitment of library personnel. The results also showed that work itself had significant influence on affective commitment of library personnel in public universities in South-West, Nigeria. In addition, the findings revealed that supervision, salary and recognition had positive and significant influence on continuance commitment of library personnel in public universities in South-West, Nigeria. The results revealed that recognition and work itself had positive and significant influence on normative commitment of library personnel in public universities in South-West, Nigeria. Level of security had a negative and significant influence on normative commitment of library personnel in public universities in South-West, Nigeria. The study concluded that job satisfaction increased organizational commitment of library personnel in public universities. It was recommended that library management should create an enabling environment and ensure regular promotion of the personnel. Originality/Value: The study has been able to establish that low commitment could be as a result of lack of job satisfaction. The results may be useful to university management who wish to enhance commitment of their personnel.